Matrimonio cristiano ante la nueva cultura jurídica - Benlloch Poveda, Antonio ("Iustitia et iudicium" ; 1, 2010)
The Christian conception about matrimoniy and family, an institution of great universal acceptance has been subject to much challenge in these days. The author tries to evaluate different concepts of matrimony and their importance to social life